A theoretical study of the tautomerism kinetics of 4-amino-6-methyl-3-thioxo-3, 4-dihydro-1, 2, 4-triazin-5(2H)-one in the gas phase: NBO population and NICS analysis. (4th March 2019) - Marzi, Mahrokh; Shiroudi, Abolfazl; Pourshamsian, Khalil; Oliaey, Ahmad Reza; Hatamjafari, Farhad
ABSTRACT: The tautomerization reactions of the 4-amino-6-methyl-3-thioxo-3, 4-dihydro-1, 2, 4-triazin-5(2 H )-one studied by means of M06-2 x and CBS-QB3 theoretical methods. The measured energy profiles are complemented with kinetic rate coefficients calculations using transition state theory (TST). In line with the optimized tautomers geometries using the CBS-QB3 method, the natural bond orbital (NBO) analysis reveals that the stabilization energies of non-bonding LP(e)S8 to the σ*N2–C3 antibonding orbitals increase from tautomers1 to2 . Furthermore, the delocalization energies of LP(e)S8 →σ*N2–C3 could explain the increase of LP(e)S8 non-bonding orbitals occupancies in the tautomers1 and2 (2 > 1). The increase of LP(e)S8 →σ*N2–C3 delocalizations could fairly explicate the kinetics of tautomeric pathways1 and2 ( k 2  >  k 1 ). Moreover, the HOMO–LUMO energy gap is increased parallel with the decreasing of activation energy barriers. NBO results also show that the kinetics of these processes controlled using LP→ σ * resonance energies. Furthermore, nucleus-independent chemical shift (NICS) indices show the calculated reaction and energy barriers are involved by changes in aromaticity characters as well as electron transfer from LP(e)S8 to σ*N2–C3 orbitals, thus these reactions are controlled from both thermodynamic and kinetic viewpoints by the changes aromaticity characters. GRAPHICAL ABSTRACT: